Energy transfer from phycobilisomes to photosystem I at room temperature - Avratanu Biswas; Avratanu Biswas; Avratanu Biswas; Parveen Akhtar; Petar H. Lambrev; Ivo H.M. van Stokkum (Frontiers in Plant Science, 2024)
The phycobilisomes function as the primary light-harvesting antennae in cyanobacteria and red algae, effectively harvesting and transferring excitation energy to both photosystems. Here we investigate the direct energy transfer route from the phycobilisomes to photosystem I at room temperature in a mutant of the cyanobacterium Synechocystis sp. PCC 6803 that lacks photosystem II. The excitation dynamics are studied by picosecond time-resolved fluorescence measurements in combination with global and target analysis. Global analysis revealed several fast equilibration time scales and a decay of the equilibrated system with a time constant of ≈220 ps. From simultaneous target analysis of measurements with two different excitations of 400 nm (chlorophyll a) and 580 nm (phycobilisomes) a transfer rate of 42 ns-1 from the terminal emitter of the phycobilisome to photosystem I was estimated.